Cooperating to Commercialize Technology: A Dynamic Model of Fairness Perceptions, Experience, and Cooperation - vanBurg, Elco; vanOorschot, Kim E. (Production and Operations Management, 2013)
Technology entrepreneurship is an important driver of economic growth, although entrepreneurs must maintain cooperative ties with the owners of any technology they hope to bring to market. Existing studies show that fairness perceptions have a great influence on this cooperation, but no research investigates its precise mechanisms or dynamic patterns. This study explores the development of 17 ventures that cooperated with a university‐owner of technology and thereby identifies different cooperation patterns in which fairness perceptions influence the degree of cooperation. These perceptions also change over time, partly as a function of accumulated experience and learning. A system dynamics model integrates insights from existing literature with the empirical findings to reveal which cooperation mechanisms relate to venture development over time; the combinations of individual experience, fairness perceptions, and market circumstances lead to four different patterns. This model can explain changes in entrepreneurial cooperation as a result of changes in fairness perceptions, which depend on learning effects and entrepreneurial experience. Each identified cooperation pattern has implications for research and offers insights for practitioners who need to manage relationships in practice.